Preparation and physical chemistry characterization of new nanostructured oxides catalysts by spray pyrolysis method for the biodiesel production - Lanfredi, Silvania [UNESP]; Djurado, Elisabeth; Nobre, Marcos A. L. [UNESP] (Trans Tech Publications, 2018)
In this work were synthesized new catalysts of stoichiometries Sr0.8K0.2TiCu0.10O3, Sr0.7K0.3TiCu0.15O3 and Sr0.5K0.5TiCu0.25O3 by spray pyrolysis method. The synthesis conditions were optimized to obtain single phase powder of titanates of double perovskite structure, with an ultrasound vibration frequency of 1.3 MHz at 700°C under air flow. The average crystallite size of the powders, determined by the Scherrer equation and using the Jade Plus 8 software, was at around 9 nm. The powder morphology was analyzed by scanning electron microscopy (SEM). The Sr0.5K0.5TiCu0.25O3 system showed particles with smooth surfaces, spherical and with smaller agglomerates than Sr0.8K0.2TiCu0.10O3, Sr0.7K0.3TiCu0.15O3 systems. This phenomenon suggests that the stoichiometry changes the aspect of the particle surface, which may influence in the catalytic activity. Thus, particles without roughening and smaller size can act as promising catalysts.
Keywords: Double perovskites; Spray pyrolysis method; Titanates; X-ray diffraction